Prevalence and factors associated with gingivitis among secondary school adolescents in Acapulco, Mexico - Bello-Castañón, Amairany (2025)
Objective: To estimate the prevalence of gingivitis and its associated factors among students at a public secondary school in Acapulco, Mexico. Materials and methods: A cross-sectional epidemiological study was conducted in February 2024 among 105 third-grade students from a public secondary school in Acapulco, Mexico. A self-administered questionnaire was applied, and a periodontal clinical examination was performed based on the classification of biofilm-induced gingival diseases. Crude and adjusted prevalence ratios were calculated using bivariate and multivariate analyses with the Mantel-Haenszel method. Results: The prevalence of gingivitis was 35.2% (n = 37/105), and all cases were localized. Two factors were associated with gingivitis: female sex (aPR = 2.19; 95% CI: 1.06-3.16) and toothbrushing fewer than three times per day (aPR = 2.32; 95% CI: 1.11-4.83). Conclusion: Gingivitis prevalence was moderate and exclusively localized. Female sex and toothbrushing fewer than three times per day were the main associated factors. These findings highlight the need to implement school-based strategies to prevent gingivitis and promote oral health among adolescents.